The Legal Concept of the State’s Right over Public Property in Libyan Legislation (Journal of human and social sciences, 2017)
This study aims to analyze the legal concept of the state’s right over public property in Libyan legislation, focusing on the criteria distinguishing public from private property and elucidating the legal nature of this right. The researcher adopts an inductive and deductive approach to analyze legal texts, judicial rulings, and legal doctrine. The study concludes that public property in Libya is defined by its allocation for public utility, whether de facto, by law, or by administrative decision. It also confirms that the state’s right to own public property is an ordinary right of ownership but subject to specific restrictions aimed at achieving public interest. Finally, the study recommends enhancing legal protection for public property and establishing clear regulations for its allocation and deallocation.
Keywords: Public Funds; State's Right; Libyan Legislation; Public Benefit; Public Ownership